The Role of Counseling Guidance Teachers in Improving Student Discipline at Mts Riyadlul Ulum Bangil - Fauziah, Mufied; Abidin, Zainal (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2023)
The teacher's task in the activity of increasing discipline in learning is very important. Because this activity is not solely the task of the teacher in class, but all teachers. Based on the results of observations at Mts Riyadlul Ulum Bangil showed that there were students who committed violations of school rules. Guidance Counseling Teachers have a big role in tackling student disciplinary violations. The approach used in this study is a qualitative descriptive approach. The results of this study are, First, Guidance and Counseling Services at Mts Riyadlul Ulum is carried out as a form of providing guidance and counseling services to the service target, namely students. In this regard, there are a number of services in guidance and counseling in schools including orientation, information, placement and distribution services, group counseling, individual counseling, group guidance, consulting services. Second, the role of the BK teacher is that the role of the teacher is not only limited to activities in class or teaching, but is broader than that. One way is through participation in guidance and counseling programs in schools. Third, the role of the counseling teacher in increasing student discipline in Mts Riyadlul Ulum, namely by implementing school rules according to the rules that apply, so as to create order and student compliance with school rules and provide sanctions for students who violate school rules.